2012
DOI: 10.1159/000343434
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Adenomas Associated with Hepatic Granulomas: Experience in Five Cases

Abstract: We present five cases in whom two rare entities were simultaneously found within the liver, i.e. hepatocellular adenomas (HCAs) and granulomas. Coexistence of both entities confuses diagnosis. Our aim is to disclose the association between HCA and hepatic granulomas. Five patients presented with HCA for which they underwent resection. During laparotomy or at pathological examination, granulomas were found in tumorous and non-tumorous tissue. No specific cause for the granulomas was found. Immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Bieze et al reported 5 hepatocellular adenomas (HCA) with granulomas in the tumor stroma and/or background liver tissue. Since 4 of them were inflammatory type HCA, they pointed to the impact of prolonged chronic inflammatory stress (27). Unlike this report, the inflammatory infiltrate score was minimal for 4 of 5 cases except Case 4 with case (Case 5) are supportive histologic features of the host reply to tumor antigens.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Bieze et al reported 5 hepatocellular adenomas (HCA) with granulomas in the tumor stroma and/or background liver tissue. Since 4 of them were inflammatory type HCA, they pointed to the impact of prolonged chronic inflammatory stress (27). Unlike this report, the inflammatory infiltrate score was minimal for 4 of 5 cases except Case 4 with case (Case 5) are supportive histologic features of the host reply to tumor antigens.…”
Section: Discussioncontrasting
confidence: 65%
“…Drugs are also reported as a causative factor of granulomas in hepatocellular lesions. Ichikawa et al recorded chemo embolic lipiodol droplets, while others reported the role of oral contraceptives (OC) (11,27). None of the granulomatous cases had neoadjuvant therapy or OC history in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Iron [74] or other pigments such as lipofuscin granules, Dubin Johnson pigment [7, 8, 16, 84], hematopoiesis, calcifications [85], and inflammatory granulomas [8688] are occasionally observed in HCA. Iron is located in hepatocytes in the Fanconi anemia.…”
Section: Hca With Rare or Misleading Featuresmentioning
confidence: 99%
“…It was proposed that the hepatic granulomas in these cases are a response to persistent inflammation caused by (inflammatory) HA, a local reaction to a neoplasm, chronic use of OCs, or a combination of these factors. In our HA case, the patient has OC use history and HA has typical morphologic features of inflammatory subtype (17).…”
Section: Discussionmentioning
confidence: 93%
“…Another uncommon morphologic feature is the granulomatous reaction in the hepatic adenoma. In literature, granuloma formation was seen in a few cases, some of them associated with oral contraceptive use, the others were present in inflammatory type HA (17,18). It was proposed that the hepatic granulomas in these cases are a response to persistent inflammation caused by (inflammatory) HA, a local reaction to a neoplasm, chronic use of OCs, or a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%